2003
DOI: 10.1001/archfaci.5.6.503
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and Histologic and Histochemical Properties of the Superior Pharyngeal Constrictor Muscle in Velocardiofacial Syndrome

Abstract: Background: Velocardiofacial syndrome (VCFS) is one of the most common multiple anomaly syndromes in humans. Pharyngeal hypotonia, one of the most common findings in VCFS, contributes to hypernasal speech, which occurs in approximately 75% of individuals with VCFS. Objective: To evaluate the thickness and histologic and histochemical properties of the superior pharyngeal constrictor (SPC) muscle in patients with VCFS to determine whether a muscle abnormality exists that might contribute to the hypotonia seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 22 publications
3
43
2
2
Order By: Relevance
“…This is not surprising given evidence of broader neuromotor differences in VCFS including smaller diameter and reduced thickness of the superior pharyngeal constrictor muscle, brain abnormalities (e.g., cerebellum, thalamus), generalized hypotonia and motor delays [17][18][19][20] . Future research should continue to investigate VP structural and timing differences in a larger sample of children with VCFS to determine if this is seen in the broader population or is a reflection of a subgroup within the syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…This is not surprising given evidence of broader neuromotor differences in VCFS including smaller diameter and reduced thickness of the superior pharyngeal constrictor muscle, brain abnormalities (e.g., cerebellum, thalamus), generalized hypotonia and motor delays [17][18][19][20] . Future research should continue to investigate VP structural and timing differences in a larger sample of children with VCFS to determine if this is seen in the broader population or is a reflection of a subgroup within the syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…These vascular anomalies have been cited as potentially dangerous risks when pharyngeal surgery is being planned [MacKenzie-Stepner et al, 1987;Mitnick et al, 1996;Tatum et al, 2002]. It has also been reported that the muscle tissue in the pharynx has abnormally small fiber size and abnormal distribution of fiber type [Zim et al, 2003]. All of these factors have been cited as risk factors for the development of velopharyngeal insufficiency and hypernasal speech.…”
Section: Clinical Features and The Vcfs Phenotypementioning
confidence: 99%
“…Finally, it has also been described that tonsils are commonly enlarged in patients with VCFS. In some cases, when tonsil tissue grows in the superior aspect, it can interfere with velopharyngeal closure during speech [14][15][16][23][24][25].…”
Section: Q112dsmentioning
confidence: 99%